Use of e-learning platforms in the training of professionals - Leonid Arsenovych; Andrii Gurzhii; Liubov Kartashova; Kyryl Shcherbyna; Maryna Semenkova (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2026)
Digital educational environments that offer adaptability, accessibility, the potential for simulation-based learning, and automated progress monitoring are progressively mitigating the constraints of traditional training models that predominantly emphasize face-to-face interaction. The objective of this study is to evaluate the efficacy of contemporary e-learning platforms in the training of professionals engaged in the field of critical infrastructure, taking into consideration regulatory, technological, and organizational factors. The study used a mixed methodology, encompassing a survey of 47 representatives of educational and government institutions; a comparative analysis of five digital platforms (Moodle CLMS TsNTU, Microsoft Learn for Educators, CISA Virtual Learning Portal, OPSWAT Academy, NSDC-authored courses); and a content analysis of the functional components of the learning environment (availability of cyber ranges, SCORM support, micro-credentials, language adaptation, and Learning Analytics). The findings revealed that the most pronounced positive influence on the quality of the educational process stemmed from the availability of adaptive simulations, Ukrainian-language content, and analytical tools for tracking the results. The scientific novelty of this study lies in the formulation of a comprehensive model for assessing the effectiveness of digital educational platforms grounded in an interdisciplinary analysis, which combines regulatory requirements, technological readiness, and pedagogical practices. Prospects for further research encompass the development of national criteria for the accreditation of online courses within high-risk sectors, the establishment of an integrated repository of simulation training materials, and the experimentation with hybrid training models predicated on adaptive scenarios and cyberfields.